Identification of Cancer Hallmarks Based on the Gene Co-expression Networks of Seven Cancers - Yu, Ling-Hao; Huang, Qin-Wei; Zhou, Xiong-Hui (Frontiers in Genetics, 2019)
Identifying the hallmarks of cancer is essential for cancer research, and the genes involved in the cancer hallmarks are more likely to be cancer drivers. However, there is still no appropriate method to solve this problem, especially considering the interrelation among the genes. Here, we mined the conservative communities existing in the gene co-expression networks of seven cancers as hallmarks candidates based on the hypothesis that the dense cluster in the gene co-expression network of cancer patients may work as a functional unit in the the process of cancer formation and progression, and the communities existing in the co-expression networks of multiple cancers may be cancer hallmarks. Functional annotation of these communities showed they were mainly related to immune response, cell cycle and the biological processes that maintained the basic function of a cell. Survival analysis using the genes in some communities verified that these hallmarks could distinguish the prognosis of cancer patients in multiple kinds of cancers. Furthermore, the genes involved in these hallmarks, one of which was related to cell cycle, could benefit the screening of cancer drugs.